Analisis Waktu Tunggu Pasien Operasi Elektif di Instalasi Bedah Sentral (IBS) dengan Metode Root Cause Analysis (RCA) di RS Bhayangkara Ruwa Jurai Lampung Tahun 2025 - Teguh Astanto; Apri Sunadi; Eka Yoshida (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
The Central Surgical Installation (CSI) plays a strategic role in ensuring the quality of hospital services, particularly in supporting the implementation of elective surgical procedures. Excessive waiting time beyond the established standards poses a serious challenge that may affect patient safety and service efficiency. This study aims to analyze the causes of delayed elective surgery waiting times at Bhayangkara Ruwa Jurai Hospital, Lampung, and to formulate solutions based on managerial and evidence-based approaches. This research employed a descriptive qualitative method using Root Cause Analysis (RCA) and the 5M factors (Man, Material, Machine, Method, Money). Data were collected through observation, interviews, and document reviews, and analyzed. The findings revealed that the average waiting time for elective surgery patients was 50 minutes, with some cases reaching up to 219 minutes. The delays were caused by a combination of factors, including a shortage of surgical and CSSD personnel, limited sterile linen, equipment failures such as operating lights and sterilization machines, non-standardized preoperative procedures, and suboptimal supervision and coordination among units. Furthermore, the work environment and limited number of operating rooms exacerbated the problem. RCA results indicated that comprehensive improvements could potentially reduce waiting times by 25–30%. This study recommends strengthening healthcare service aspects through staff training, procurement of additional equipment, establishment of standardized SOPs, and integration of inter-unit communication systems. Improvements in the work environment and data-driven planning are essential to enhance the quality of surgical services and significantly reduce delays.